DWT and IDWT Using Secret Key and Watermarking with in Video Compression - SHOBA, G.; JEYALAKSHMY, G. (IJRDO -Journal of Computer Science Engineering, 2016)
In this paper, Authenticatingwatermarking is nothing but inserting a hiddenobject in order to detect deceitful alteration byhackers. The object may be in terms of a secretkey or password etc. There are quite fewnumbers of authentication methods areavailable for videos. Resent developers indigital video and internet technology helps thecommon user to easily produce illegal copiesof videos. In order to solve the copyrightprotection problem and deceitful alteration byhackers of videos, several watermarkingschemes have been widely used. Very fewauthenticating of watermarking schemes havebeen produced for defining the copyrights ofdigital video. The process of Digitalwatermark embeds the data called watermarkin digital media like image, video, audio fileetc. so that it can be claimed for rights. Thepaper represents the complete softwareimplementation of 3-Level DWT algorithmsand to have more secure data a secret key isused. The secret key is given to watermarkimage during embedding process and whileextracting the watermark image the samesecret key is used. To check effectiveness ofthe watermark video MSE and PSNRparameters are used.